Reduced Risk-Taking following Disruption of the Intraparietal Sulcus - Coutlee, Christopher G.; Kiyonaga, Anastasia; Korb, Franziska M.; Huettel, Scott A.; Egner, Tobias (Frontiers in Neuroscience, 2016)
Decision makers frequently encounter opportunities to pursue great gains – assuming they are willing to accept greater risks. Previous neuroimaging studies have shown that activity in the intraparietal sulcus (IPS) and the inferior frontal junction (IFJ) are associated with individual preferences for economic risk (“known unknowns,” e.g., a 50% chance of winning 5) and ambiguity (“unknown unknowns,” e.g., an unknown chance of winning 5), respectively. Whether processing in these regions causally enables risk-taking for individual decisions, however, remains unknown. To examine this question, we assessed the decision to engage in risk-taking after disrupting neural processing in the IPS and IFJ of healthy human participants using repetitive transcranial magnetic stimulation. While stimulation of the IFJ resulted in general slowing of decision times, disrupting neural processing within the IPS selectively suppressed risk-taking, biasing choices towards certain options featuring both lower risks and lower expected rewards. Our results are the first to demonstrate the necessity of intact IPS function for choosing uncertain outcomes when faced with calculable risks and rewards. Engagement of IPS during decision making may support a willingness to accept uncertain outcomes for a chance to obtain greater gains.